Research as mission: Experiences and expectations of mission agency leadership regarding the ministry role of clinical and public health research - Carlan Wendler; Doug Lindberg; Greg Sund (Health for All Nations, 2022)
Introduction: Research as a focus of healthcare missions is an important component of the evolving role of healthcare missionaries and sending organizations in LMICs. There is a lack of data and understanding on what appetite exists to expand and invest in such research initiatives. Methods: This study surveyed leaders of North American mission sending agencies engaged in healthcare, seeking to ascertain their current and anticipated future involvement in research, education, and healthcare delivery. Results: Forty-seven leaders responded (of 211 contacted) to our survey of whom 37 completed all survey questions. Eighty-two percent of respondents agreed that they had a responsibility as an organization to study how to improve clinical care and public health. Sixty-four percent of respondents anticipated reduced healthcare delivery in the next 10 years. During that same 10-year, time frame, 61% anticipate an increase in health research mentoring, and 79% expect an increased role of student education. However, this emerging shift towards research and education is not yet reflected with a similar degree of perceived enthusiasm among missionaries in doing research or donors in supporting it. Discussion: Across the spectrum of middle- and upper-level leadership in a variety of missions sending organizations, there is recognition of an important and increasing role for healthcare research activities in ministry. About half of the agencies represented in our sample are already involved in research and will need to share best practices with others as healthcare missionaries devote more time and attention to research mentorship. Done well, this can provide additional avenues for disciple-making in both home and host cultures as well as improve the care for populations in those remote and rural areas often most served by healthcare missionaries. Conclusion: Research as mission has, heretofore, been a neglected methodology, but institutional leaders in healthcare missions anticipate an increasingly important ministry role for it.